2023
DOI: 10.21203/rs.3.rs-2468246/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving breastfeeding support through the implementation of the baby friendly hospital and community initiatives: a scoping review

Abstract: Background Improved breastfeeding practices have the potential to save the lives of over 823,000 children under 5 years old globally every year. The Baby-Friendly Hospital Initiative (BFHI) is a global campaign by the World Health Organization and the United Nations Children's Fund, which promotes best practice to support breastfeeding in maternity services. The Baby-Friendly Community Initiative (BFCI) grew out of step 10, with a focus on community-based implementation. The aim of this scoping review is to m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 157 publications
0
3
0
Order By: Relevance
“…We found that explanation of the benefits of breastfeeding by health professionals, the intention to feed, and the practice of feeding in congruence to a mother's intention during pregnancy were associated with exclusive breastfeeding. This is consistent with different Health Problems of Civilization eISSN: 2354-0265, ISSN: 2353-6942 studies that found that breastfeeding counseling to mothers and antenatal education programs were significantly related to exclusive breastfeeding [1,7,11,27,45,46] and that inadequate knowledge about breastfeeding was considered an important barrier to exclusive breastfeeding in studies conducted in Sri Lanka [32], in the state of Qatar [37], and in Saudi Arabia [28].…”
Section: Resultssupporting
confidence: 87%
“…We found that explanation of the benefits of breastfeeding by health professionals, the intention to feed, and the practice of feeding in congruence to a mother's intention during pregnancy were associated with exclusive breastfeeding. This is consistent with different Health Problems of Civilization eISSN: 2354-0265, ISSN: 2353-6942 studies that found that breastfeeding counseling to mothers and antenatal education programs were significantly related to exclusive breastfeeding [1,7,11,27,45,46] and that inadequate knowledge about breastfeeding was considered an important barrier to exclusive breastfeeding in studies conducted in Sri Lanka [32], in the state of Qatar [37], and in Saudi Arabia [28].…”
Section: Resultssupporting
confidence: 87%
“…In comparison to conventional medical facilities, hospitals that are attuned to fertility concerns tend to adhere more to evidence-based practices that encourage lactation and intimate mother-infant bonding. Empirical research has indicated that the prevalence of exclusive breastfeeding is notably higher in regions where a substantial number of hospitals and maternal health care facilities advocate for fertility-friendly services (12). This correlation contributes significantly to the improvement of neonatal health outcomes.…”
Section: Characteristics and Advantagesmentioning
confidence: 99%
“…For the postnatal period, it is important to highlight that the tenth Step of the BFHI provides the extension to the Baby-Friendly Community Initiative (BFCI), which focuses on the community-based support needed after discharge. Despite its relevance, there is less evidence about the implementation of BFCI (12).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have documented that countries have encountered difficulties in sustaining the BFHI because of financial and human resources considerations (14). It has also been noted that its successful implementation requires political commitment (12). Additionally, successfully implementing the Ten Steps can be challenging due to the lack of robust internal monitoring and evaluation systems at maternity facilities that can support quality assurance efforts related to the Ten Steps (14), including the training of health personnel (20,21).…”
Section: Introductionmentioning
confidence: 99%